2006
DOI: 10.1136/bmj.38922.516204.55
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceptions of written consent: questionnaire study

Abstract: Objective To examine patients' understanding of the status, function, and remit of written consent to surgery. Design Prospective questionnaire study. Questionnaires were sent to patients within one month of surgery. Responses were analysed with frequencies and single variable analyses. Setting Large teaching hospital. Participants 732 patients who had undergone surgery in obstetrics and gynaecology over a six month period. Main outcome measures Patients' awareness of the legal implications of written consent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
4
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 8 publications
10
78
4
4
Order By: Relevance
“…It is implicitly evident, however, that the need to acquire a signature for completion of the consent process is (14) an additional task to complete before the procedure and may therefore be viewed negatively by the staff. It is clear from this study that staff working within the endoscopy suite actually view the added step as beneficial for patients before they undergo invasive procedures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is implicitly evident, however, that the need to acquire a signature for completion of the consent process is (14) an additional task to complete before the procedure and may therefore be viewed negatively by the staff. It is clear from this study that staff working within the endoscopy suite actually view the added step as beneficial for patients before they undergo invasive procedures.…”
Section: Discussionmentioning
confidence: 98%
“…The form states that you understand and are giving us permission to go ahead with this procedure.'' Immediately after the procedure (performed without sedation in every case), every patient was required to complete a standardized questionnaire adapted for use in this study from a validated questionnaire used previously in a similar study [14]. The questionnaire for those not signing a consent form (Table 1a) differed somewhat syntactically from that given to those signing a consent form (Table 1b) to reflect that they had not been asked to sign anything.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings concur with studies that have examined consent for surgery 7,9,10 in that patient recollection of the consent discussion is often poor and that fundamental misconceptions about the consent process remain prevalent. 7,11,12 Recall of consent discussions for anaesthesia has also been shown to be poor in the few studies that have examined this. A recent single-centre study of parental recall of information given at the time of consent discussions demonstrated that recollection of anaesthesia-related information was generally poor but improved when consent was obtained by an anaesthesia care provider.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies in which the rate of reading the ICD was low, 60% of the patients stated that ICD was a document -piece of paper -arranged to protect the hospital and the doctor and to give the initiative in the decision making process to the doctor. Another piece of information received from these patient groups was that the patients thought that signing the ICD was a legal necessity in which they handed their legal rights to the hospital and the doctor, and that if they refused to sign it, they would not have the operation; also, they thought that they could not change their minds after signing the ICD (5,16). Also in our study, "paying no attention" and "not finding time" were the two most common reasons for not reading the ICD, even though in our polyclinic, patients were called in the order in which they handed in their ICD.…”
Section: Discussionmentioning
confidence: 99%